2024
DOI: 10.21203/rs.3.rs-3897238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mendelian randomization distinguished the changes in gut microbiota caused by IBD from those that lead to IBD

Fan Li,
Xiaoping Han,
Tongyu Tang
et al.

Abstract: Observational studies have reported that dysbiosis of gut microbiota may be a contributing factor in the development of IBD. However, the causal relationship between gut microbiota and IBD remains unclear due to the coexistence of gut dysbiosis in IBD patients. The aim of this study is to investigate the causal and reverse causal relationships between gut microbiota and inflammatory bowel disease (IBD).We aimed to explore the causal and reverse causal relationships between gut microbiota and IBD using a two-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These findings suggest that Clostridia vadinBB60 group may have anti-inflammatory properties. Consistent with this notion, two studies have reported that Clostridia vadinBB60 group is protective in IBD 42,43 .…”
Section: Discussionmentioning
confidence: 60%
“…These findings suggest that Clostridia vadinBB60 group may have anti-inflammatory properties. Consistent with this notion, two studies have reported that Clostridia vadinBB60 group is protective in IBD 42,43 .…”
Section: Discussionmentioning
confidence: 60%